Pengaruh Konservatisme Akuntansi dan Financial Distress terhadap Penghindaran Pajak dengan Karakteristik Eksekutif sebagai Variabel Moderasi - Deby Kustia Pratiwi; Atik Djajanti (Sekolah Pascasarjana Perbanas Jakarta, 2021)
This study was conducted to analyze the effect of accounting conservatism and financial distress on tax avoidance with executive characteristics as a moderating variable in companies listed on the Indonesia Stock Exchange (IDX) for the period 2017 to 2019. The sampling technique in this study was purposive sampling. A total of 22 companies were obtained as samples and met the criteria of the research sample. The analysis technique used in testing the data hypothesis is Moderated Regression Analysis (MRA) and t-statistics to test the partial regression coefficients and f-statistics to test the effect together with a significance level of 5% (0.05). The analytical program used is XLSTAT version 2014. The results obtained in this study indicate that (1) Accounting Conservatism has a positive effect on Tax Avoidance; (2) Financial distress has a negative effect on Tax Avoidance; (3) Executive characteristics do not affect the relationship between Accounting Conservatism and Tax Avoidance; (4) Executive Characteristics strengthen the influence of Financial Distress relationship on Tax Avoidance. Keywords: Accounting Conservatism, Financial Distress, Tax Avoidance and Executive Characteristics